Frequency of Sleep Disorders and Their Association with Neurocognitive, Psychological, or Physical Alterations in Postmenopausal Women - Álvaro Monterrosa-Castro; Andrea Castilla-Casalins; Mayra Colmenares-Gúzman; Peter Chedraui (Journal of Mid-Life Health, 2025)
Objective: The objective of the study was to determine the frequency of sleep disorders and their association with neurocognitive, psychological, or physical alterations in postmenopausal Colombian women. Materials and Methods: A cross-sectional study carried out on postmenopausal women (50–75 years). Participants were surveyed on a general questionnaire, the Jenkins Sleep Scale, the Mini-Mental State Examination tool, the Menopause Rating Scale (MRS), and the Strength, Assistance with walking, Rising from a chair, Climbing stairs, and Falling scale. Crude and adjusted logistic regression analyses were performed to determine the association between sleep problems (dependent variable) with the neurocognitive, psychological, and physical established impairments (independent variables). The covariates were age, age at menopause, years of being postmenopausal, coffee consumption, smoking habit, and nutritional status. Results: Among 601 participants, 53 (8.8%) had sleep problems. Bivariate analysis found that overall impairment of quality of life and its domains (somato-vegetative, psychological, and urogenital), and cognitive impairment and its various aspects (memory, language, fixation, and temporal fixation) were found at a higher rate among women with sleep problems. The risk of sarcopenia was similar among those with and without sleep problems. Adjusted logistic regression determined that sleep problems were associated with somato-vegetative (odds ratio [OR]: 3.44, 95% confidence interval [CI]: 1.56–7.59), urogenital (OR: 2.35, 95% CI: 1.00–5.51) and cognitive impairment (OR: 2.20, 95% CI: 1.02–4.71). Conclusion: 8.8% of this sample of postmenopausal women had sleep problems, which were significantly associated with impairment of quality-of-life aspects and cognition.